2013
DOI: 10.1152/ajpcell.00078.2012
|View full text |Cite
|
Sign up to set email alerts
|

Heme modulates intestinal epithelial cell activation: involvement of NADPHox-derived ROS signaling

Abstract: Barcellos-De-Souza P, Moraes JA, de-Freitas-Junior JC, MorgadoDíaz JA, Barja-Fidalgo C, Arruda MA. Heme modulates intestinal epithelial cell activation: involvement of NADPHox-derived ROS signaling. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Furthermore, heme induces ROS generation dependent on enzymatic reactions. In fact, it was demonstrated that heme triggers ROS production by the NADPH oxidase enzyme (Graça-Souza et al, 2002; Arruda et al, 2004; Moraes et al, 2012; Barcellos-de-Souza et al, 2013) and by mitochondria (unpublished), through activation of specific signaling pathways (Graça-Souza et al, 2002; Porto et al, 2007; Fernandez et al, 2010; Fortes et al, 2012). Alternatively, heme-induced formation of radical species relies on the conversion of low-reactive organic hydroperoxides (ROOH) into highly reactive alkoxyl (RO•) and peroxyl (ROO•) radicals (Tappel, 1953, 1955; Van der Zee et al, 1996).…”
Section: Direct Cytotoxic Effects Of Hemementioning
confidence: 99%
“…Furthermore, heme induces ROS generation dependent on enzymatic reactions. In fact, it was demonstrated that heme triggers ROS production by the NADPH oxidase enzyme (Graça-Souza et al, 2002; Arruda et al, 2004; Moraes et al, 2012; Barcellos-de-Souza et al, 2013) and by mitochondria (unpublished), through activation of specific signaling pathways (Graça-Souza et al, 2002; Porto et al, 2007; Fernandez et al, 2010; Fortes et al, 2012). Alternatively, heme-induced formation of radical species relies on the conversion of low-reactive organic hydroperoxides (ROOH) into highly reactive alkoxyl (RO•) and peroxyl (ROO•) radicals (Tappel, 1953, 1955; Van der Zee et al, 1996).…”
Section: Direct Cytotoxic Effects Of Hemementioning
confidence: 99%
“…Compelling evidence from the literature shows that many of the inflammatory and cytotoxic effects exerted by heme are mediated by ROS that can be generated by enzymatic as well as nonenzymatic reactions (9,17,27,28). As an important source of cellular stress, an excess of ROS also has been implicated as a trigger for protein aggregation (29,30).…”
Section: To Test Whether P62mentioning
confidence: 99%
“…In pathological conditions that result in hemolysis, rhabdomyolysis, or extensive cell damage, large amounts of hemeproteins are released, and under oxidative conditions, the heme moiety is released, further increasing oxidation and cellular stress (7,8). Recently, it was shown that heme can induce the generation of reactive oxygen species (ROS) through the activation of NADPH oxidase (9) or by the mitochondria (10), and that blocking these pro-oxidant effects protects the host from cell damage and tissue injury.…”
mentioning
confidence: 99%
“…ROS generated by heme has been mainly attributed to the Fenton reaction. However, recent studies suggest that heme can generate ROS through multiple sources, including NADPH oxidase and mitochondria (22,(24)(25)(26)(27).…”
mentioning
confidence: 99%